Productivity and Technical Efficiency in Islamic Banks: Cross - Country Analysis - Romdhane, Mohamed; Alhakimi, Saif Sallam (Asian Journal of Economic Modelling, 2017)
In this paper, we use the decomposed Malmquist index to analyze in depth the productivity of 36 Islamic banks in 15 countries before and after the international financial crisis, during the 2003-2011 periods. This analysis shows that productivity fluctuated over time for the same bank, and it varied from one region to another. Banks in the Gulf countries are the most efficient. In all Islamic banks, technical efficiency was the main cause of improving productivity and had helped to increase the volume of intermediation.